2018
DOI: 10.1080/09688080.2018.1472486
|View full text |Cite
|
Sign up to set email alerts
|

Dualities between Tunisian provider beliefs and actions in abortion care

Abstract: Despite Tunisia's historically progressive reproductive health policies, Tunisian women now face significant challenges accessing legal abortion. Through in-depth interviews with providers at six facilities, we explored factors influencing provider attitudes about abortion and provider perspectives about abortion morality, safety, and legality. We found that gatekeepers (counsellors and front office staff) generally believed abortion was immoral, while obstetricians and gynecologists were more likely to suppor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 13 publications
1
17
0
Order By: Relevance
“…Twenty-six studies ( Aniteye and Mayhew, 2013 ; Cárdenas et al, 2018 ; de Vries et al, 2020 ; Doran and Hornibrook, 2014 ; Esia-Donkoh et al, 2015 ; Fathallah, 2019 ; Freedman et al, 2010 ; Freeman and Coast, 2019 ; Harden and Ogden, 1999 ; Heller et al, 2016 ; Homaifar et al, 2017 ; Hulme-Chambers et al, 2018 ; Izugbara et al, 2015; Izugbara et al, 2017 ; Kimport et al, 2016 ; LaRoche et al, 2020 ; Margo et al, 2016 ; Nandagiri, 2019 ; Marlow et al, 2014 ; Påfs et al, 2020 ; Payne et al, 2013 ; Pheterson and Azize, 2008 ; Raifman et al, 2018 ; Schwandt et al, 2013 ; Ushie et al, 2019 ; Weitz and Cockrill, 2010 ) described instances of providers acting as gatekeepers to abortion care, including actions taken to actively discourage abortion seekers from accessing services. About one-third of these studies ( de Vries et al, 2020 ; Fathallah, 2019 ; Freeman and Coast, 2019 ; Freedman et al, 2010 ; Heller et al, 2016 ; Homaifar et al, 2017 ; Hulme-Chambers et al, 2018 ; Kimport et al, 2016 ; Margo et al, 2016 ; Pheterson and Azize, 2008 ) focused on matters directly related to the delivery of timely services or issues related to geography (i.e.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Twenty-six studies ( Aniteye and Mayhew, 2013 ; Cárdenas et al, 2018 ; de Vries et al, 2020 ; Doran and Hornibrook, 2014 ; Esia-Donkoh et al, 2015 ; Fathallah, 2019 ; Freedman et al, 2010 ; Freeman and Coast, 2019 ; Harden and Ogden, 1999 ; Heller et al, 2016 ; Homaifar et al, 2017 ; Hulme-Chambers et al, 2018 ; Izugbara et al, 2015; Izugbara et al, 2017 ; Kimport et al, 2016 ; LaRoche et al, 2020 ; Margo et al, 2016 ; Nandagiri, 2019 ; Marlow et al, 2014 ; Påfs et al, 2020 ; Payne et al, 2013 ; Pheterson and Azize, 2008 ; Raifman et al, 2018 ; Schwandt et al, 2013 ; Ushie et al, 2019 ; Weitz and Cockrill, 2010 ) described instances of providers acting as gatekeepers to abortion care, including actions taken to actively discourage abortion seekers from accessing services. About one-third of these studies ( de Vries et al, 2020 ; Fathallah, 2019 ; Freeman and Coast, 2019 ; Freedman et al, 2010 ; Heller et al, 2016 ; Homaifar et al, 2017 ; Hulme-Chambers et al, 2018 ; Kimport et al, 2016 ; Margo et al, 2016 ; Pheterson and Azize, 2008 ) focused on matters directly related to the delivery of timely services or issues related to geography (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…Eight of the 26 studies spoke to issues linking gatekeeping and user-centred care ( Doran and Hornibrook, 2014 ; Esia-Donkoh et al, 2015 ; Harden and Ogden, 1999 ; Hulme-Chambers et al, 2018 ; LaRoche et al, 2020 ; Påfs et al, 2020 ; Raifman et al, 2018 ; Weitz and Cockrill, 2010 ). Participants described the unacceptable nature of facing providers who were reluctant or refused to provide care ( Doran and Hornibrook, 2014 ; Påfs et al, 2020 ; Raifman et al, 2018 ; Weitz and Cockrill, 2010 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…19 The study also revealed ambivalence, if not opposition, from some ONFP administrative or political staff. 20 These obstacles have never been solved, although the institution itself is the country's main agency in charge of the regulation and institutionalization of these policies.…”
Section: Current Obstacles To Accessing Abortionmentioning
confidence: 99%